EFFECTS OF GROWTH STAGES ON THE NUTRITIVE VALUE OF SPECIFIC HALOPHYTE SPECIES IN SALINE GRASSLANDS - S. Temel; M. Surmen; M. Tan (Journal of Animal and Plant Sciences, 2015)
Halophytes adapting to extreme environmental factors provide an important part of forage requirements for livestock grazing in early spring, summer and especially in late autumn. But many wild halophyte species are undervalued mainly because of insufficient knowledge about their potential feeding value and yields. Information on nutritive values and forage yields of species in different phenological stages is important in terms of grazing management. Thus dry hay yield per plant, and crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL), dry matter digestibility (DMD), digestible energy (DE) and metabolizable energy (ME) of Salicornia europaea, Salsola dendroides, Salsola nitraria, Salsola oppositifolia, Suaeda microphylla, Suaeda altissima, Petrosimonia brachiata and Alhagi pseudalhagi in early vegetative and seed maturity stage were investigated in this study. Research was conducted in a factorial arrangement of a completely randomized block design with three replications in saline rangelands of Turkey’s Igdir Plain. Results showed that phonological stages and species had a significant effect on all traits (P<0.01). While the highest yields per plant were produced in Salsola dendroides, the highest nutritional values were obtained from Suaeda microphylla and Salicornia europaea. It was determined that CP, DMD, DE and ME contents decreased with the maturation of plants while yields per plant as well as NDF, ADF and ADL increased. As a result, it was found both phenological stages were suitable for grazing in terms of nutritional value, and all species could be supplied a considerable amount and quality of forage compared to conventional fodder resources.
Keywords: Forage quality and yield; growth stage; livestock feeding; saline grazing lands